Functionalized Graphene and Cobalt Phthalocyanine Based Materials with Potential Use for Electrical Conduction - Cardenas-Jiron, G (Springer Netherlands, 2014)
In this work we investigate at the density functional theory level (B3PW91, B3LYP, M05-2X) the electrical properties of complexes formed by cobalt phthalocyanine (CoPc) and cobalt tetraaminophthalocyanine (CoTAPc) adsorbed on functionalized graphene (FG). As functionalization are studied the carboxylate (18 complexes), epoxide (three complexes), hydroxyl (three complexes) and carboxyl (two complexes) groups. Three models of graphene molecules are used; pristine, defect (Def), and vacancy (Vac), leading to a total of 26 complexes. We studied three main orientations for the interaction graphene-phthalocyanine; parallel, perpendicular and extended. Binding energies show a very large stability for G-COO?-CoTAPc complexes (~-100 to -150 kcal/mol) in an extended orientation and a little lower for G-O-CoPc and G-OH-CoPc in a parallel orientation (~-20 to -65 kcal/mol). No adsorption of CoPc occur on G-COOH. HOMO-LUMO Gap (HLG) show higher values for the complexes than the fragment FG when the functionalization COO- is by the edge of graphene; giving account of a favorable adsorption of CoPc (CoTAPc) in agreement with the binding energies. For epoxide and hydroxyl (except for G-Vac) where the functionalization is on the center of G, we found that HLG is shorter in ~0.5 eV with respect to FG (~4 eV). The high HLG values for these complexes suggest that the adsorption of CoPc is completely favorable. Several of these complexes present an electron acceptor species (FG) and an electron donor species (CoPc, CoTAPc). For the stable complexes, we found a higher current conduction for the parallel orientation. Thus, complexes with carboxylate functionalization present a conduction of ~7 µA similar for hydroxyl (~7 µA) but some lower than for epoxide (~18 µA). The results have shown that the adsorption of cobalt phthalocyanines on functionalized graphene is feasible; yielding a tunable hybrid material that allows sensing because of the intrinsic electrical properties provided by functionalized G and CoPc. © Springer Science+Business Media Dordrecht 2014.
Keywords: Cobalt phthalocyanine; Current-voltage; Graphene oxide; Molecular orbitals; Sensor